2006
DOI: 10.1016/j.ecss.2006.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyoplankton dynamics in the Guadiana estuary and adjacent coastal area, South-East Portugal

Abstract: The species composition, abundance and distribution of the ichthyoplankton of the Guadiana estuary and adjacent coastal area were studied in relation to several environmental parameters. Sampling occurred during new moon Spring tides, at the ebb and flood, at nine stations, from March 2002 to February 2003. Temperature, salinity, dissolved inorganic macronutrients, seston and organic matter and chlorophyll a were determined at each station. A total of 22 and 34 fish eggs and larvae taxa were identified, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 35 publications
5
51
1
1
Order By: Relevance
“…Despite the higher abundance of the three species (D. sargus, S. pilchardus and P. microps), we found lower diversity and abundance of the overall fish larvae community compared with previous surveys carried out in adjacent areas of the Guadiana estuary (Chícharo et al 2000 andFaria et al 2006). However, in these studies, captures exclusively near our sampling area had diversity and abundance values much closer to our observations.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Despite the higher abundance of the three species (D. sargus, S. pilchardus and P. microps), we found lower diversity and abundance of the overall fish larvae community compared with previous surveys carried out in adjacent areas of the Guadiana estuary (Chícharo et al 2000 andFaria et al 2006). However, in these studies, captures exclusively near our sampling area had diversity and abundance values much closer to our observations.…”
Section: Discussioncontrasting
confidence: 55%
“…Chícharo et al (2000) reported for the sampling point "Carrasqueira creek" (a marsh creek a few meters from our sampling site) the presence of 5 different species and an abundance peak of 143 larvae/100 m 3 in March 2000. Values observed by Faria et al (2006) for the lower estuary were slightly higher, with 19 different species and a maximum abundance of 285 larvae/100 m 3 in June 2002. Diversity in the salt marsh creek agreed well with descriptions in the literature for other European marshes, where few species were found.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the Guadiana estuary, a community shift has been already documented, including plankton and fish [9,11,12]. In addition, first occurrences of several marine invasive species have also been recorded, with potentially detrimental effects on native biota [13].…”
Section: Introductionmentioning
confidence: 97%
“…The larvae of Sparidae were among the most abundant in this lagoon, and most of these larvae were post-flexion larvae collected during flood tides (Chícharo and Teodósio, 1991). So, the absence of a meaningful number of pre-flexion larvae and the presence of post-flexion larvae during flood tides suggests that spawning does not occur inside the lagoon, as observed for other species in an estuary located nearby (Faria et al, 2006;Morais et al, 2009). Larvae's ingress mechanisms were never evaluated, so larvae's ingress could result from purely stochastic events (e.g., winds, tides) (Hare et al, 2005;Schieler et al, 2014) or due to active ingress strategies (e.g., selective tidal stream transport, bottom-inflow ingress, or ingress near the bottom or margins where water velocity is slower) which include ingress during flood tides (Hare et al, 2005).…”
Section: Response Of Sparus Aurata Larvae To Odor Cuesmentioning
confidence: 99%